Demanding disability – an analysis of opportunities and threats related to the functioning of people with mild intellectual disabilities Part 1 - Parys, Katarzyna; Olszewski, Sławomir (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Katarzyna Parys, Sławomir Olszewski, Demanding disability – an analysis of opportunities and threats related to the functioning of people with mild intellectual disabilities. Part 1. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 15–38. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.01 The thesis considered in the article is the statement that mild intellectual disability is a demanding disability. Three dimensions were distinguished in the description of the situation of persons with a mild intellectual disability: 1. Attributes of the phenomenon of mild intellectual disability 2. Attributes of the population of people with mild intellectual disabilities 3. Attributes of selected elements of the mesosystem of people with mild intellectual disabilities The key phenomena for these dimensions were analysed. The ambiguity of these phenomena has become the basis for considering the opportunities and threats that they may pose. Due to the extensiveness of the issues raised, the issues discussed are presented in two parts. The present text is considers the first two of the dimensions listed.